Computational fluid dynamics modelling of cerebrospinal fluid pressure in Chiari malformation and syringomyelia - Clarke, Elizabeth C.; Fletcher, David F.; Stoodley, Marcus A.; Bilston, Lynne E. (Journal of biomechanics, 2013)
The pathogenesis of syringomyelia in association with Chiari malformation (CM) is unclear. Studies of patients with CM have shown alterations in the CSF velocity profile and these could contribute to syrinx development or enlargement. Few studies have considered the fluid mechanics of CM patients with and without syringomyelia separately. Three subject-specific CFD models were developed for a normal participant, a CM patient with syringomyelia and a CM patient without syringomyelia. Model geometries, CSF flow rate data and CSF velocity validation data were collected from MRI scans of the 3 subjects. The predicted peak CSF pressure was compared for the 3 models. An extension of the study performed geometry and flow substitution to investigate the relative effects of anatomy and CSF flow profile on resulting spinal CSF pressure. Based on 50 monitoring locations for each of the models, the CM models had significantly higher magnitude (p<0.01) peak CSF pressure compared with normal. When using the same CSF input flow waveform, changing the upper spinal geometry changed the magnitude of the CSF pressure gradient, and when using the same upper spinal geometry, changing the input flow waveform changed the timing of the peak pressure. This study may assist in understanding syringomyelia mechanisms and relative effects of CSF velocity profile and spinal geometry on CSF pressure.